Pengaruh Gamifikasi dalam Pembelajaran Menulis Cerpen Siswa Kelas XI 2 SMA Negeri 8 Makassar - Ahmad Fadil; Aswati Asri; Nurhusna Nurhusna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by the low short story writing skills of students in Indonesian language learning which is still conventional and less involving student activity. This study aims to analyze the effect of the gamification method on the short story writing skills of class XI 2 students at SMA Negeri 8 Makassar. The type of research used is a quantitative research type using a pre-experimental method. The data collection technique in this study is a short story writing assignment which is divided into pre-test and post-test. Data analysis used in this study is descriptive statistical analysis and inferential statistical analysis. The results of the study revealed that the learning outcomes of short story writing texts of class XI 2 students of SMA Negeri 8 Makassar before the application of the gamification method were in the sufficient category with an average value of 53.08. The learning outcomes of short story writing texts of class XI 2 students of SMA Negeri 8 Makassar after the application of the gamification method were in the good category with an average value of 81.71. Based on the results of the paired t-test, it can be concluded that the implementation of the gamification method significantly improved the short story writing skills of grade 11 students at SMA Negeri 8 Makassar.